Two cases with dysferlinopathy - Gaye Eryaşar; Yaprak Seçil; Yeşim Beckmann; Ayşen İnceoğlu Kendir; A. Gülden Diniz; Mustafa Başoğlu (Türk Nöroloji Dergisi, 2011)
Dysferlinopathy includes a rare spectrum of muscle disease characterized by two main phenotypes: Miyoshi myopathy(MM) and Limb Girdle muscular dystrophy(LGMD 2B) and results from a mutation of the gene that codes dysferline protein (DYSF gene, 2p13). In this report, we present 2 cases with dysferlinopathy whose diagnosis were confirmed by clinical and muscle biopsy findings.